Pilot Phase II study of mazindol in children with attention deficit/hyperactivity disorder - Konofal E; Zhao W; Laouénan C; Lecendreux M; Kaguelidou F; Benadjaoud L; Mentré F; Jacqz-Aigrain E (Dove Medical Press, 2014)
Eric Konofal,1,2 Wei Zhao,3–5 Cédric Laouénan,5–7 Michel Lecendreux,1,2 Florentia Kaguelidou,3–5 Lila Benadjaoud,4 France Mentré,5–7 Evelyne Jacqz-Aigrain3–51Pediatric Sleep Disorders Center, 2Child and Adolescent Psychiatric Department, 3Department of Pediatric Pharmacology and Pharmacogenetics, Hôpital Robert Debré, Assistance Publique – Hôpitaux de Paris (APHP), 4Clinical Investigation Center, Institut National de la Santé et de la Recherche Médicale (INSERM), 5Université Paris Diderot, Sorbonne Paris Cité, Paris, 6INSERM, Infection, Antimicrobiens, Modélisation, Evolution (IAME), UMR1137, Paris, 7Department of Biostatistiques, Hôpital Bichat, APHP, Paris, FranceObjective: Mazindol has been proposed as a potential treatment of children with attention deficit/hyperactivity disorder (ADHD). The purpose of this pilot study was to assess its pharmacokinetics, short-term efficacy, and safety.Subjects and methods: A total of 24 children (aged 9–12 years) with ADHD (according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, text-revision criteria) received a daily dose of 1 mg for 7 days and were followed for 3 additional weeks. Pharmacokinetic samples were collected after the first administration. ADHD symptoms were assessed using the ADHD Rating Scale (RS)-IV, Conners’ Parent Rating Scale – Revised: Long (CPRS-R:L) at screening, baseline, and the end of the study. The Clinical Global Impression – Severity (CGI-S) scale was assessed at baseline, and the CGI – Improvement (CGI-I) scale was assessed at subsequent visits.Results: Twenty-one subjects (aged 10±1 years) were analyzed. Pharmacokinetic data were described by a one-compartment model with first-order absorption, elimination, and lag time. The typical apparent clearance and apparent volume of distribution were 27.9 L/h and 234 L, and increased with fat-free mass and age, respectively. The mean change in score in ADHD RS-IV after 1 week of mazindol was −24.1 (P<0.0001), greater than a 90% improvement from baseline. Reduction of CPRS-R:L and CGI-S scores were −52.1 (P<0.0001) and −2.5 (P<0.01), respectively. Adverse events were mild to moderate, decreased appetite and upper abdominal pain being the most common.Conclusion: This preliminary study shows that mazindol might be an effective, well-tolerated, and long-acting (more than 8 hours) agent for the treatment of ADHD in children.Keywords: pharmacokinetics, efficacy, safety, mazindol, ADHD, pediatrics